Stages of Agricultural Commercialization in Uganda: The Role of the Markets - Oleg Nivievskyi; Stephan von Cramon-Taubadel; Sergiy Zorya (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2010)
Agricultural commercialization has become the centerpiece of the sector development strategy in Uganda in recent years. Nevertheless the low market participation of most smallholders in the country remains a fact. We employ semi-parametric regression techniques to analyze the current state of market participation and production diversification and to identify the determinants of commercialization in Uganda. We find that the key constraint to agricultural commercialization in Uganda is inadequate access of farmers to infrastructure and assets, both physical and human. Those with access to assets and closer to markets engage actively in the markets, while those lacking one or more of these essential ingredients largely do not. These findings are in line with the recent literature on smallholder market participation in Africa. We also find that commercialization proceeds in stages. When farmers have appropriate incentives and access to markets, they do not immediately separate production and consumption decisions. Instead they first diversify their production portfolios before subsequently increasing commercial specialization. The result is a U-shaped relationship between commercialization and diversification.
Keywords: 330; commercialization; diversification; smallholder agriculture; Uganda; semi-parametric regression